Abnormal erythroid maturation leads to microcytic anemia in the TSAP6/Steap3 null mouse model. Issue 3 (March 2015) - Blanc, Lionel; Papoin, Julien; Debnath, Gargi; Vidal, Michel; Amson, Robert; Telerman, Adam; An, Xiuli; Mohandas, Narla
<x xml:space="preserve">Abstract</x> Genetic ablation of the ferrireductase STEAP3, also known as TSAP6, leads to severe microcytic and hypochromic red cells with moderate anemia in the mouse. However, the mechanism leading to anemia is poorly understood. Previous results indicate that TSAP6/Steap3 is a regulator of exosome secretion. Using TSAP6/Steap3 knockout mice, we first undertook a comprehensive hematologic characterization of the red cell compartment, and confirmed a dramatic decrease in the volume and hemoglobin content of these erythrocytes. We observed marked anisocytosis as well as the presence of fragmenting erythrocytes. Consistent with these observations, we found by ektacytometry decreased membrane mechanical stability of knockout red cells. However, we were unable to document significant changes in the expression levels of the major skeletal and transmembrane proteins to account for this decrease in the membrane stability. Furthermore, there were no differences in red cell survival between wild type and knockout animals. However, when we monitored erythropoiesis, we found a decreased number of proerythroblasts in the bone marrow of TSAP6/Steap3−/− animals. In addition, progression from the proerythroblastic to the orthochromatic stage was affected, with accumulation of cells at the polychromatic stage. Altogether, our findings demonstrate that abnormal erythroid maturation is the main cause of anemia in these mice. Am. J. Hematol. 90:235–241, 2015. © 2014 Wiley Periodicals, Inc.